A large-scale drug screen identifies selective inhibitors of class I HDACs as a potential therapeutic option for SHH medulloblastoma. Issue 9 (16th May 2019) - Pak, Ekaterina; MacKenzie, Ethan L; Zhao, Xuesong; Pazyra-Murphy, Maria F; Park, Paul M C; Wu, Lei; Shaw, Daniel L; Addleson, Emily C; Cayer, Suzanne S; Lopez, Begoña G-C; Agar, Nathalie Y R; Rubin, Lee L; et al.
Abstract: Background: Medulloblastoma (MB) is one of the most frequent malignant brain tumors of children, and a large set of these tumors is characterized by aberrant activation of the sonic hedgehog (SHH) pathway. While some tumors initially respond to inhibition of the SHH pathway component Smoothened (SMO), tumors ultimately recur due to downstream resistance mechanisms, indicating a need for novel therapeutic options. Methods: Here we performed a targeted small-molecule screen on a stable, SHH-dependent murine MB cell line (SMB21). Comprehensive isotype profiling of histone deacetylase (HDAC) inhibitors was performed, and effects of HDAC inhibition were evaluated in cell lines both sensitive and resistant to SMO inhibition. Lastly, distinct mouse models of SHH MB were used to demonstrate pharmacologic efficacy in vivo. Results: A subset of the HDAC inhibitors tested significantly inhibit tumor growth of SMB21 cells by preventing SHH pathway activation. Isotype profiling of HDAC inhibitors, together with genetic approaches suggested that concerted inhibition of multiple class I HDACs is necessary to achieve pathway inhibition. Of note, class I HDAC inhibitors were also efficacious in suppressing growth of diverse SMO inhibitor‒resistant clones of SMB21 cells. Finally, we show that the novel HDAC inhibitor quisinostat targets multiple class I HDACs, is well tolerated in mouse models, and robustly inhibits growth of SHH MB cells in vivo as well as in vitro. Conclusions: Our data provide strong evidence that quisinostat or other class I HDAC inhibitors might be therapeutically useful for patients with SHH MB, including those resistant to SMO inhibition.